Challenges of religious tourism in Palestine / Badaruddin Mohamed and Jafar Suleiman - Mohamed, Badaruddin; Suleiman, Jafar (Universiti Teknologi MARA (UiTM), Malaysia, 2011)
Palestine, the home of the world's three major religions: Islam, Judaism, and Christianity. Hence, considers the first center of tourism due to the faithful of these three major world faiths flocking to Palestine to engage in sacred pilgrimages. Some of these sites which are frequently visited are Jerusalem, Nazareth, Jericho, Bethlehem and Hebron. Palestine was for many centuries a destination of pilgrims and visitors of Muslims and Christians from all over the world. Unfortunately, Palestine after the 1948 war fell under Israeli occupation and was exposed to many catastrophes up until this time; all this led to the instability and the decrease in the number of tourists to Palestine; which had become a dangerous area which reduced the flow of tourism in general. At the same time, came the peace negotiations between the PLO (Palestinian liberation organization) and Israel in Oslo which was signed in Washington in 1993. In this period there was an economic recovery and tourism in the Palestinian territories, especially in the West Bank and Gaza Strip started to once again flourish. The Primary purpose of this paper is to display the significance of the religious tourism in Palestine and influence of the Israeli occupation on religious tourism and restrictions of movement and freedom for visitors and the local community to visit those holy sites and also how it effects the tourism market growth, also the measures which are used and their negative impact on all tourism. This paper concludes to that Palestine is unique, due to its history, heritage, culture, geographic location, environment and religions. This study suggests to the ministry of tourism and antiquities in Palestine to create new ways to protect the Islamic and Christian places in Palestine as well as to invite new tourists to visit it and experience dark tourism in Palestine which focuses on historical atrocities inflicted on the Palestinian people and their quest for equality and freedom.